2016
DOI: 10.1088/1367-2630/18/10/103012
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal coherence of non-equilibrium multimode photon condensates

Abstract: We report on the observation of quantum coherence of Bose-Einstein condensed photons in an optically pumped, dye-filled microcavity. We find that coherence is long-range in space and time above condensation threshold, but short-range below threshold, compatible with thermalequilibrium theory. Far above threshold, the condensate is no longer at thermal equilibrium and is fragmented over non-degenerate, spatially overlapping modes. A microscopic theory including cavity loss, molecular structure and relaxation sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…For condensates of polaritons, mixed states of matter and light, polarization symmetry breaking was reported [7,8], while polariton arrays have shown phase locking [9]. Further, spatial coherence has been reported for equilibrium photon condensates [10], and also in a nonequilibrium regime [11]. Both atomic and polariton condensates are usually assumed to emit a single wave train of constant amplitude [1,12].…”
mentioning
confidence: 99%
“…For condensates of polaritons, mixed states of matter and light, polarization symmetry breaking was reported [7,8], while polariton arrays have shown phase locking [9]. Further, spatial coherence has been reported for equilibrium photon condensates [10], and also in a nonequilibrium regime [11]. Both atomic and polariton condensates are usually assumed to emit a single wave train of constant amplitude [1,12].…”
mentioning
confidence: 99%
“…They were able to show that the multimode condensation seen in Ref. [37] was due to imperfect clamping of the molecular excited-state population in regions adjacent to the central condensate light mode which leaves the possibility of positive gain for other modes.…”
Section: A Nonequilibrium Model Of Photon Condensationmentioning
confidence: 97%
“…The small mode volume of the system allows self‐diffusion that quickly circulates photobleached dye molecules out of the cavity mode, in which the authors demonstrated CW operation of a dye laser without externally driven recirculation, with single mode tunability over a bandwidth of 20 nm. In parallel with dye‐based microlasers, dye molecules incorporated in cavities were also investigated for photon condensations, wherein the photons can reach thermal equilibrium through frequent energy exchanges with the thermal bath of dye–solvent vibrations . Walker et al.…”
Section: Exciton‐polaritons In Open‐access Microcavitiesmentioning
confidence: 99%
“…In parallel with dye-based microlasers, dye molecules incorporated in cavities were also investigated for photon condensations, wherein the photons can reach thermal equilibrium through frequent energy exchanges with the thermal bath of dye-solvent vibrations. [128][129][130][131][132] Walker et al reported nonequilibrium BEC of a very small number (7 ± 2) of photons in the chip-based open-access microcavity incorporating dye molecules. [133] The concave mirror, with a RoC of 400 µm fabricated by FIB milling, was specifically designed to form a photonic potential of 2D harmonic oscillator that enabled the observation of a multimode condensate regime of photons that exhibit strong intermode correlations.…”
Section: Dye Lasers and Photon Condensationsmentioning
confidence: 99%